Analisis Tauriyah Mujarradah dalam Al-Quran Surah Al-Anam Ayat 60: Sebagai Bentuk Makna yang Dekat Maupun Makna yang Jauh - Dicky Syahfrizal; Aziz Isroq (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This paper aimed to research about Badi‟ style in al-Qur‟an‟s passages. This research used one aspects of Balaghah, tauriyah, and spoke about alQur‟an‟s passages which contains tauriyah style dan the secret behind its using. The objects of this research come from al-Qur‟an‟s passages using style of language/balaghah analysis, especially Ilmu Badi‟ which concentrated to beauty of meaning (muhassinaat ma’nawiyyah) and importance of understanding tauriyah for another studies focused their object based on al-Qur‟an, directly or not. This paper find that there are at least 10 passages which contains tauriyah in al-Qur‟an, they are al-Baqarah: 143, al-An‟am: 60, at-Taubah: 21, Yunus: 92, Yusuf: 42, Yusuf: 96, Thaha: 5, adz-Dzariyat: 47, ar-Rahman: 6 and al-Ghasiyah: 8. This number of passages erase the old paradigm that recognite only 3 passages in alAn‟am: 60, Thaha: 5 and adz-Dzariyat: 47. Understanding tauriyah became important in Tafsir studiy and isthinbatu’l ahkaam in Ushu‟l Fiqh field, even became one of obligatory requirements for mujtahid.